Insights on climate change in a business university setting: a case of Environmental Management students - Mahadih Kyambade; George William Mugerwa; Afulah Namatovu (Cogent Education)
This study investigates the perspectives of Makerere University Business School (MUBS) students enrolled in the Environmental Management (EM) course on climate change. Using a focus group methodology, the research explored the attitudes and perceptions of 22 third-year Bachelor of Leadership and Governance students. Guiding questions rooted in climate change policy decision-making were employed to facilitate discussion. The findings reveal that all students displayed a strong awareness of both local and global climate change issues. Their environmental engagement ranged from recycling and reducing energy consumption to advocating for school-wide energy-saving initiatives, such as the installation of thermal energy generators. Students also reported noticeable shifts in local climate patterns, with many expressing concern over rising global temperatures and future environmental risks. Varied opinions emerged regarding the anthropogenic causes of climate change, with some students attributing it to natural cycles, while others recognized human activity as a significant contributor. This research provides valuable managerial insights for academic institutions, emphasizing the need to integrate climate change education into the curriculum and promote student-led environmental initiatives. Additionally, it underscores the importance of addressing climate change perceptions to foster greater collective action among students. This study contributes to the limited body of knowledge on climate change perspectives in university settings, particularly in Uganda.